Evidence of positive selection and concerted evolution in the rapidly evolving PRDM9 zinc finger domain in goats and sheep. (13th September 2016) - Ahlawat, S.; Sharma, P.; Sharma, R.; Arora, R.; Verma, N. K.; Brahma, B.; Mishra, P.; De, S.
Summary: Meiotic recombination contributes to augmentation of genetic diversity, exclusion of deleterious alleles and proper segregation of chromatids. PRDM9 has been identified as the gene responsible for specifying the location of recombination hotspots during meiosis and is also the only known vertebrate gene associated with reproductive isolation between species. PRDM9 encodes a protein with a highly variable zinc finger (ZF) domain that varies between as well as within species. In the present study, the ZF domain of PRDM9 on chromosome 1 was characterized for the first time in 15 goat breeds and 25 sheep breeds of India. A remarkable variation in the number and sequence of ZF domains was observed. The number of ZF repeats in the ZF array varied from eight to 12 yielding five homozygous and 10 heterozygous genotypes. The number of different ZF domains was 84 and 52 producing 36 and 26 unique alleles in goats and sheep respectively. The posterior mean of dN/dS or omega values were calculated using thecodeml tool ofpamlx to identify amino acids that are evolving positively in goats and sheep, as positions −1, +3 and +6 in the ZF domain have been reported to experience strong positive selection across different lineages. Our study identified sites −5, −1, +3, +4 and +6 to be experiencing positive selection. Small ruminant zinc fingers were also found to be evolving under concerted evolution. Our results demonstrate the existence of a vast diversity of PRDM9 in goats and sheep, which is in concert with reports in many metazoans.